Wireless Ambulatory Esophageal pH Monitoring in Dogs with Clinical Signs Interpreted as Gastroesophageal Reflux. (30th September 2014) - Kook, P.H.; Kempf, J.; Ruetten, M.; Reusch, C.E.
<x xml:space="preserve">Abstract</x> Background Although gastroesophageal reflux (GER) often is assumed to be causative for upper gastrointestinal and respiratory signs in dogs, no attempts have been made to verify this assumption. Objectives To monitor esophageal pH with the Bravo pH system in healthy dogs and client‐owned dogs displaying signs commonly attributed to GER. Animals Seven healthy and 22 client‐owned dogs. Methods After routine esophagogastroduodenoscopy, radiotelemetric pH capsules were placed in distal esophagus for continuous pH recording. Reflux was defined as single pH measurement <4. At discharge, owners were instructed to press individually predefined clinical sign‐buttons on the receiver whenever indicated. Results between groups were compared using Mann–Whitney U‐test. Results The median (range) number of refluxes in client‐owned and healthy dogs, respectively, was 17 (1–205) and 10 (1–65), the number of refluxes >5 minutes in duration was 1 (0–14), and 1 (0–4), duration of longest reflux (min) was 10 (0–65) and 8 (0–27), and fractional time pH <4 (%) was 0.76% (0.01–6.28), and 0.3% (0–3.1). No differences were found between groups. The median of 7 (1–35) clinical sign‐button pushes were recorded in 21 dogs. Median of 12.5% (2.8% [1/35]–50% [2/4]) reflux‐positive clinical sign‐button pushes was found in 10 dogs with reflux‐positive pushes. Five (22.7%) dogs had increased esophageal acid exposure, and mild esophagitis was noted in 1 dog. Conclusion and Clinical Importance Despite evidence of increased GER in some dogs, the clinical sign‐reflux association remained poor. Future investigation should focus on dogs with esophagitis.